Issue linkage and trade policy uncertainty: Evidence from trade preferences for developing countries - Stefan Suttner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2023)
This paper quantifies potential costs of issue linkage examining trade preferences granted under the US Generalized System of Preferences (GSP). Preferential market access via US GSP is conditional on political practices by beneficiaries. Using monthly import data, I study trade policy uncertainty related to country-level GSP eligibility reviews conducted by the US administration. For cases initiated between 2003 and 2019, I find negative effects for trade flows from countries under review despite the fact that applied tariffs remained unchanged during the review process. The estimated trade effects of eligibility reviews are sizable and larger for less differentiated product categories. Placebo events before reviews yield no trade effects. The results suggest that trade policy uncertainty induced by issue linkage may undermine trade-promoting incentives of trade preferences at stake.
Keywords: F13; F14; O19; 330; Trade Policy Uncertainty; Trade Preferences; Generalized System of Preferences; Developing Countries; Issue Linkage